Identifying Key Factors Influencing the Development of Higher Order Thinking Skills (HOTS) in Students: A Systematic Literature Review - Ismeirita Ismeirita; Eeng Ahman; Dadang Dahlan; Dedi Supendra (STAI Hubbulwathan Duri, 2025)
Higher-order thinking skills (HOTS), encompassing critical thinking, creative thinking, and problem-solving, are essential competencies for 21st-century learners. Despite extensive research, a holistic synthesis of the multidimensional factors influencing HOTS remains limited. This study employed a Systematic Literature Review (SLR) following PRISMA guidelines to identify and analyze factors affecting HOTS. A total of 42 peer-reviewed articles indexed in Scopus, published between 2014 and 2024, were reviewed. Articles were assessed for quality using CASP and JBI checklists, and thematic analysis was conducted using NVivo software. Analysis revealed six main dimensions influencing HOTS: individual, learning environment, teacher, curriculum, contextual and cultural, and affective, encompassing 16 sub-themes. The individual dimension emerged as the most influential (26%), followed by learning environment (24%), teacher (23%), curriculum (11%), contextual and cultural (9%), and affective (7%). The findings highlight the multifaceted nature of HOTS development, with particular emphasis on internal student attributes and teacher competence. Practical implications include the need for personalized learning approaches, enhanced teacher training in problem-based pedagogy, and adaptive, culturally responsive curricula. These insights can inform educational policy and classroom practice aimed at fostering HOTS across educational levels.